COUGH: REVIEW OF A SYMPTOM WITH SEVERAL DIAGNOSTIC POSSIBILITIES (International Seven Journal of Health Research, 2024)
INTRODUCTION: Cough is a habitual reflex of the respiratory tract to an aggression, representing one of the main defense mechanisms of the respiratory tract. However, although important for the maintenance of homeostasis, the cough mechanism becomes pathological when dysregulated. OBJECTIVE: The present study aimed to clarify a path between the epidemiological issues of cough, the pathophysiological mechanisms, semiology, possible etiologies, clinical behavior and therapeutic approach to cough. METHODS: this is a narrative review of the literature, carried out in the first half of 2021, focusing on studies related to cough, its pathophysiological and etiological mechanisms, in addition to the clinical and therapeutic approach, through searches in the PubMed, SciELO, Medline/LILACS/Bireme databases, using the descriptors: cough, acute cough, subacute cough and chronic cough. RESULTS AND DISCUSSION: Cough is a frequent symptom worldwide, and is considered the most common reason for seeking medical care. The mechanism of cough is a result of the integration of the components of the neurophysiological pathways, respiratory muscles, and pulmonary mechanics and fluid mechanics.  For the initial approach to cough, it is essential to extract a detailed clinical history and thorough physical examination, since the most common causes of cough are easily identifiable with a good anamnesis, being classified according to the duration of the complaint as acute, subacute and chronic. The therapeutic approach to cough, as a symptom, is vast, sometimes imprecise, and changes according to the time of onset and etiology of the condition. FINAL CONSIDERATIONS: Acute and chronic cough can aggravate and trigger different complications, but among all the possible complications, the change in lifestyle and the significant impact on the quality of life of the individual affected by cough is evident.